Proposal to conserve the name Salpichroa against Nectouxia (Solanaceae) - Barboza, Gloria Estela (2016)
To conserve the name Salpichroa against Nectouxia (Solanaceae) is proposed. This proposal is a consequence of recent taxonomic and phylogenetic work with the Salpichroina clade. A more complete sampling of Salpichroa species has shown that Salpichroa is not monophyletic as currently circumscribed, since Nectouxia is nested within it. As Nectouxia has priority over Salpichroa, the transfer of all Salpichroa species to Nectouxia would necessitate more than 20 name changes, including for a widespread global weed, S. origanifolia, which appears on noxious weed lists in several countries. The conservation of the later generic name Salpichroa would necessitate a single name change for Nectouxia formosa, aname that is widely used in the Mexican floristic literature for a relatively rare plant. Acceptance of this proposal would conserve the status quo and avoid disadvantageous nomenclatural changes not only in South America, but globally.